Diffusion of Al-Shabaab through ungoverned spaces: can the inkblot logic provide an explanation? - Francis Onditi (Cogent Social Sciences, 2024)
This article proposes a methodology for analyzing the social network behaviour of the extremist group (Al-Shabaab) within the context of ungoverned spaces in the Horn of Africa. Inkblot logic is introduced as an analytical framework that highlights the role of ‘loose bonds’ and ‘hard bonds’ in the geographical distribution of terrorists’ activities ranging from the group’s epicenter in Somalia to neighboring Kenya. Traditionally, policy analysts and researchers have studied the behavior of extremists on the basis of in situ, i.e. their static geographical position. However, the stasis approach assumes that extremist groups operate in fixed position relative to the perceived enemy. Yet the elusive group has been found to establish complex familial or fictive kinship networks beyond their country of origin, while maintaining a local presence embedded within communities. Hence, efforts to predict their movements and spatial distribution can prove difficult. The inkblot approach is of theoretical and practical use, as it illuminates possibilities of indirectly plotting the ‘ungoverned spaces’, hence, improving predictability of terrorists’ activities in time and space within the kinship networks.